1998
DOI: 10.1046/j.1365-2613.1998.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heat shock protein 47 is increased in remnant kidney and correlates with disease progression

Abstract: Glomerulosclerosis is characterized by accumulation of the mesangial extracellular matrix, including type I and V collagen. The processing for the collagens in the glomeruli may play a critical role for development of glomerulosclerosis. We examined the expression of heat shock protein 47 (HSP47), a collagen-binding molecular chaperone in the progressive glomerulosclerosis model. Subtotally nephrectomized rats, unlike sham-operated rats, developed focal and segmental glomerulosclerosis. Immunological staining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 22 publications
(32 reference statements)
1
26
0
Order By: Relevance
“…However, its role in kidney diseases in relation to sclerosis/ fibrosis in diabetic nephropathy and IgA nephropathy is completely unknown. We and others (8,28) have demonstrated that HSP47 in glomerulosclerosis is associated with collagen staining. Furthermore, the blocking of HSP47 with antisense oligonucleotides caused a dramatic amelioration of glomerular lesions in the rat glomerulonephritis model (9).…”
Section: Quantitation Of the Expression Ratio Of Hsp47/gapdh Mrna Andmentioning
confidence: 67%
See 2 more Smart Citations
“…However, its role in kidney diseases in relation to sclerosis/ fibrosis in diabetic nephropathy and IgA nephropathy is completely unknown. We and others (8,28) have demonstrated that HSP47 in glomerulosclerosis is associated with collagen staining. Furthermore, the blocking of HSP47 with antisense oligonucleotides caused a dramatic amelioration of glomerular lesions in the rat glomerulonephritis model (9).…”
Section: Quantitation Of the Expression Ratio Of Hsp47/gapdh Mrna Andmentioning
confidence: 67%
“…We recently reported that the expression of HSP47 was markedly increased in parallel with the development of glomerulosclerosis in a rat renal ablation model (8). We also found that the inhibition of HSP47 ameliorated glomerulosclerosis (9).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…The spatiotemporally concerted expression of HSP47 with collagens is also observed during mouse and chick embryonic development (10). In addition, a marked induction of HSP47 has been reported in the progression of fibrosis in various experimental fibrosis models, including liver cirrhosis (11), kidney fibrosis (12), and atherosclerosis (13). The down-regulation of hsp47 caused by introducing hsp47 antisense oligoribonucleotides into rat renal cells after the initiation of fibrosis markedly reduces the rate of the progression of fibrosis and reduces the levels of types I and III collagens in the kidney (14).…”
mentioning
confidence: 95%
“…This early role must be significant. Increased Hsp47 expression has been linked to a number of diseases in which increased collagen deposition occurs, including arteriosclerosis (22,23), myocardial infarction (24), and hepatic (25), renal (26), and pulmonary fibrosis (27). Indeed Sunamoto et al (28) successfully reduced the progression of glomerulonephritis in a rat model by reducing Hsp47 expression.…”
mentioning
confidence: 99%